COLLECTIVE EXECUTION AND DEJUDICIALIZATION: BETWEEN EFFECTIVENESS AND FUNDAMENTAL GUARANTEES (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
Brazilian civil enforcement has faced a historical deficit in effectiveness, reflected in the gap between the declaration of a right and its fulfillment. The 2015 Code of Civil Procedure (CPC) responded with the general executive clause (art. 139, IV), expanding the repertoire of atypical measures, while Bill 6.204/2019 proposes the dejudicialization of enforcement actions through an enforcement agent at the protest notary's office. This article investigates to what extent—and under what conditions—dejudicialization can increase efficiency without violating the defendant's fundamental rights. Methodologically, exploratory research is conducted using a literature review and qualitative data analysis. The analysis points to the suitability of a hybrid model that prioritizes patrimonial and informational means, reserves atypical measures for strictly necessary situations, with qualified motivation and a defined timeframe, and structures dejudicialization with transparent proceduralization, sufficient judicial oversight, governance, and technological interoperability. It is concluded that the combination of judicial control and standardized extrajudicial routines is capable of increasing predictability and speed of execution without sacrificing legal certainty.